Functional and phenotypical analysis of IL‐6‐secreting CD4+ T cells in human adipose tissue. Issue 3 (29th January 2018) - de Jong, Anja J.; Pollastro, Sabrina; Kwekkeboom, Joanneke C.; Andersen, Stefan N.; Dorjée, Annemarie L.; Bakker, Aleida M.; Alzaid, Fawaz; Soprani, Antoine; Nelissen, Rob G.H.H.; Mullers, Jan B.; Venteclef, Nicolas; de Vries, Niek; et al.
Abstract: Emerging evidence indicates that a dynamic interplay between the immune system and adipocytes contributes to the disturbed homeostasis in adipose tissue of obese subjects. Recently, we observed IL‐6‐secretion by CD4 + T cells from the stromal vascular fraction (SVF) of the infrapatellar fat pad (IFP) of knee osteoarthritis patients directly ex vivo. Here we show that human IL‐6 + CD4 + T cells from SVF display a more activated phenotype than the IL‐6 − T cells, as evidenced by the expression of the activation marker CD69. Analysis of cytokines secretion, as well as expression of chemokine receptors and transcription factors associated with different Th subsets (Treg, Th1, Th2, Th17 and Tfh) revealed that IL‐6‐secreting CD4 + T cells cannot be assigned to a conventional Th subset. TCRβ gene analysis revealed that IL‐6 + and IL‐6 − CD4 + T cells appear clonally unrelated to each other, suggesting a different specificity of these cells. In line with these observations, adipocytes are capable of enhancing IL‐6 production by CD4 + T cells. Thus, IL‐6 + CD4 + T cells are TCRαβ T cells expressing an activated phenotype potentially resulting from an interplay with adipocytes that could be involved in the inflammatory processes in the OA joint. Abstract : T cells are present in adipose tissue. Characterization of CD4 + T cells in several adipose tissues led to the identification of a population of cells that secretes IL‐6 directly ex vivo, is in an activated state and interacts with adipocytes. These cells could contribute to adipose tissue inflammation.